1976
DOI: 10.1113/jphysiol.1976.sp011245
|View full text |Cite
|
Sign up to set email alerts
|

The contractile properties of slow muscle fibres in sheep extraocular muscle.

Abstract: SUMMARY1. The diameters of nerve fibres in the sheep trochlear nerve were measured and they fell into two distinct groups.2. Selective stimulation of the small diameter group of nerve fibres gave rise to a slow contraction of the superior oblique muscle which was attributed to multiply innervated muscle fibres.3. The slow fibre contraction following a single stimulus to the small diameter nerves had a rise time of 20-50 msec and was 150-980 mg in size. On repetitive stimulation, a maximum slow fibre contractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

1979
1979
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…First, in the present study the type of innervation of the fibres was identified directly by the features of the synaptic activity while the mentioned authors based their identification on other criteria. As held by Pilar (1967), Barmack, Bell & Rence (1971) and Browne (1976) it is possible that these criteria were not specific for the recognition of multiple innervation. Secondly, it is conceivable that the cellular population of the muscle regions explored in the above-mentioned studies and in the present analysis were different.…”
Section: Electrical Properties Of Extraocular Musclesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, in the present study the type of innervation of the fibres was identified directly by the features of the synaptic activity while the mentioned authors based their identification on other criteria. As held by Pilar (1967), Barmack, Bell & Rence (1971) and Browne (1976) it is possible that these criteria were not specific for the recognition of multiple innervation. Secondly, it is conceivable that the cellular population of the muscle regions explored in the above-mentioned studies and in the present analysis were different.…”
Section: Electrical Properties Of Extraocular Musclesmentioning
confidence: 99%
“…Bach-y-Rita & Ito (1966) and Lennerstrand (1974) have reported that in cat extraocular muscles a large number of fibres are multiply innervated and have action potentials. The existence of such fibre type has been questioned on the basis that the criteria used for their identification were not specific enough (Pilar, 1967;Barmack, Bell & Rence, 1971;Browne, 1976). Nevertheless, a very small number of fibres that are multiply innervated and capable of firing action potentials has been identified electrophysiologically in cat (Hess & Pilar, 1963) and in rabbit extraocular muscles, in a combined histological and electrophysiological study (Ozawa, Cheng, Davidowitz & Breinin, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…They have a much slower rise in tension to tetanic nerve stimulation than twitch fibers, are very resistant to fatigue, and are suited to maintaining tension over long periods (Browne, 1976;Lennerstrand and Nichols, 1977;Morgan and Proske, 1984;Nelson et al, 1986). On the basis of these properties, the nontwitch muscle fibers would be suited to a tonic function in eye muscle control.…”
mentioning
confidence: 96%
“…Physiological studies in cats demonstrate that the EOM fibers with a multiterminal innervation do not propagate action potentials (Lennerstrand, 1975;Lennerstrand and Nichols, 1977) and are similar to other slow fibers found in birds and amphibians (Morgan and Proske, 1984). Due to their relative inaccessibility, the role of these fibers in the generation of ocular movements is poorly understood although it has been suggested that they serve to smooth and dampen the action of antagonistic muscles (Browne, 1976).…”
Section: Global Zone Fibersmentioning
confidence: 97%